MANAJEMEN LOGISTIK PADA GUDANG FARMASI RUMAH SAKIT UMUM DAERAH KABELOTA KABUPATEN DONGGALA - Pebrianti, Pebrianti (Katalogis, 2015)
This study at determining the implementation of logistics Management in Hospital Pharmacheutical Warehouse of Regional General Hospital Kabelota of District Donggala. Type of the research used is qualitative descriptive. Type of data used are primary data and secondary data. Data collection technique. Data analysis used are Miles and Huberman models, namely data reduction, data presentation and conclusion. Theory used is the theory of Donald J Bowersox, consisting of five component, namely : structure of facilities, transportation, provision of supplies, communication and handling and storage. Based on the research result, the implementation of Management in Hospital Pharmacheutical Warehouse of Regional General Hospital Kabelota of District Donggala has not been effective yet, first; inadequate facilities structure, inconsistent transportation in delivering pharmaceuticals, and the other three components such as: provision of supplies, communication and handling and storage are already fulfilled, although there are still things that need to be dealt with, so it is expected that the five components all together can be implemented optimally and effectively. Thus, the researcher concludes that the implementation of Management in Hospital Pharmacheutical Warehouse of Regional General Hospital Kabelota of District Donggala is not maximized, because all the components of logistics management is not maximized.